Gastric symptoms and low perceived maternal warmth are associated with eating disorder symptoms in young adolescent girls. Issue 6 (9th April 2021) - Kerr, Kara L.; Ralph‐Nearman, Christina; Colaizzi, Janna M.; DeVille, Danielle C.; Breslin, Florence J.; Aupperle, Robin L.; Paulus, Martin P.; Morris, Amanda Sheffield
Abstract: Objective: This study sought to determine whether gastric symptoms are associated with later eating disorder (ED) symptoms during early adolescence, and whether this relationship is moderated by parental warmth/acceptance and/or the child's sex. Method: Longitudinal data from the Adolescent Brain Cognitive Development SM Study were utilized. Participants ages 9–10 years old ( N = 4, 950; 2, 370 female) completed measures at baseline and 1 year later (Y1). At baseline, gastric symptoms were measured by parent‐reported items from the Child Behavior Checklist (CBCL), and perceived parental acceptance was measured by youth report on the Children's Report of Parent Behavior Inventory (CRPBI) Acceptance subscale separately for mothers and fathers. ED symptoms at Y1 were assessed by parent report on a computerized version of the Kiddie Schedule for Affective Disorders and Schizophrenia (K‐SADS). Linear mixed‐effects models were conducted separately for maternal and paternal acceptance to test relationships among variables. Results: A three‐way interaction between baseline gastric symptoms, sex, and maternal acceptance predicted Y1 ED symptoms (𝛽 = 0.08; p < .01). Post‐hoc analyses revealed that the interaction between gastric symptoms and maternal acceptance was significant for girls only (𝛽 = −0.06, p < .01), such that low maternal acceptance was associated with a stronger relationship between baseline gastric symptoms and Y1 ED symptoms. No statistically significant main effects or interactions were found in the model for paternal acceptance. Discussion: Gastric symptoms and low perceived maternal acceptance may interact to result in heightened risk for EDs in young adolescent girls.